### Discussion :: Problems on Ages - General Questions (Q.No.4)

Dharumaraj S said: (Jun 7, 2010) | |

(b-2)+ b + .5b =27 which is an alternate method to solve the same problem..... |

Suresh said: (Jun 16, 2010) | |

Mr Dharumaraj shall you please explain ur answer? |

Shan said: (Aug 21, 2010) | |

Hi, let c year is x then B is twice of C then, B=2x Then A is 2 years older then B, therefore now B=2x,Then A=2+B, that is A=2+2x Therefore sum up all the value:[(2+2x)for A,2x for B,x for C] therefore 2+2x+2x+x=27 5x+2=27 5x=27-2 5x=25 x=25/5 x=5 now B is directly linked with C rather then A Therefore B=2x where x=5 2*5=10 that'z it my frnd |

Sri said: (Oct 2, 2010) | |

B is twice as old as C means C=2B right? |

Raheem said: (Nov 16, 2010) | |

Who is twice as old as c means? |

Sweta said: (Dec 22, 2010) | |

We can also solve as A's age be x yrs. then B's age is x-2 and C's age is(x-2)/2. |

Prashanth said: (Jan 19, 2011) | |

Your thought is right but answer will be wrong..just watch A+B+C=27 x+x-2+(x-2)/2 = 27 2x+2x-4+x-2 = 27*2= 54 5x-6 = 54 5x= 48 Finally x=48/5 which is a wrong ans always we have to equal the x to the smallest number as per the problem.... |

Shalini said: (Feb 22, 2011) | |

I got ur explantion but in solving y cannt we take 2(2x)+2x+x=27 bcoz when i read this question i did in this way only but when after I saw this answer it was different. SO PLZ TELL ME SOME TIPS HOW 2 IDENTIFY THIS IS BELONGS 2 THIS METHODS |

Ganesh said: (Mar 4, 2011) | |

A=2+B, B=2C A+B+C=27 so (2+B) + B + B/2 = 27 2B + B/2 = 25 5B/2 = 25 B=10 |

Ilaks said: (May 17, 2011) | |

@shalini Read the ques properly. Assume C=X. it is given that A IS 2 YEARS OLDER THAN B. It means that we should ADD the 2 years to B's age, so A=B+2. Then for C it is given that it was TWICE AS OLD AS C. so it is understood tat it should be MULTIPLIED WITH THE C'S AGE. so B=2X. Finally, sub B=2X in A's equation(A=B+2). therefore A=2X+2 Now A+B+C=27, therefore sub the values of A,B,C in the equation 2X+2+2X+X=27 5X+2=27 5X=27-2 5X=25 X=5. |

Vignesh Venkatesan said: (May 18, 2011) | |

@Sri b is twice old as c means.. c=b/2 b=2c |

Wisdom said: (Jul 4, 2011) | |

a=x; b=x-2; c=(x-2)/2; a+b+c=27 x+x-2+[(x-2)/2]=27 [2x+2x-4+x-2]/2=27 5x-6=54 5x=60 x=12 b=x-2; b=10 we got answer |

Sathya said: (Aug 8, 2011) | |

Why we take c=x. Why we not take that a=x;. Please explain. |

Swetha said: (Aug 9, 2011) | |

@Sathya We can take a = x also. Whatever we take, answer 'll be same. |

Jatinder S said: (Sep 11, 2011) | |

A=B+2....1 given B=2C .......2 given from statement 2 : C=B/2 total is 27 therefor A+B+C=27 B+2+B+B/2=27 4B=50 B=10. |

Srini said: (Nov 4, 2011) | |

Can you give me short cut to solve this? |

Arokiaraj said: (Dec 4, 2011) | |

c=x b=2x a=2x+2 (2x+2)+2x+x=27 5x=25 x=25/5 x=5 b=2x b=2*5=10 |

Nagendra said: (Dec 22, 2011) | |

The population of town was 24000. If males increases by 6% and females by9%, it becomes 25620. Number of males and females are?- Please any one explain me... |

Naresh said: (Mar 5, 2012) | |

Hi dude............ females(Y)=6000,males(X)=18000 x+y=24000........................(1) (106/100)x+(109/100)y=25620.......(2) by solving this 2 u get before increasing values.......... after increasing total number of females are (109/100)*6000=6540 after increasing total number of males are (106/100)*18000=19080 total is 25620 Hence proved(any doubts?) |

Renu said: (Apr 10, 2012) | |

A+B+C=27 (B+2)+B+(B-2)=27 3B=27 B=9 |

Geetha said: (Apr 30, 2012) | |

How u get x=18000 and y=6000? How it come? 106/100 109/100 |

Kalai said: (May 7, 2012) | |

A is 2 years old than B ===> A= B+2 B is Twice as old than c ===> B=2C ==> C=B/2 A+B+C = 27 So we can write as below A+B+C = 27 B+2+B+B/2 = 27 B+B+B/2=27-2 2B+B/2=25 (4B+B)/2=25 5B=50 B=10 |

Rupinder said: (Jun 4, 2012) | |

A+B+C=27----------(1) A=B+2-------------(2) B=2C => C=B/2-----(3) Put (3),(2) in (1) =>(B+2)+B+(B/2)=27; => 2B+4+2B+B=54; => 5B=50-4; => B=10; Hope it'll help you |

Shajil George said: (Sep 12, 2012) | |

Let the age of c is x Given that the age of b is twice of c age so, b is age is 2x Similarly a is two years grater than b is age, so, a is 2x+x From the Question The sum of a,b,c is 27 Then, 2x+2+2x+x=27 5x+2=27 5x=27-2 5x=25 x=25/5 =5 So,the age of b is 2x, The value of x is 5 So the age of bis 10. |

Neeta said: (Oct 14, 2012) | |

Why can't we take B=x? if answer is same when we assume any one out of A B C =x, answer will be wrong if we assume B=x B=X A=X+2 C=2X Then A+B+C=27 X+2+X+2X=27 4X+2=27 4X=27-2 X=25/4 X=6.25 |

Mourya said: (Jul 28, 2013) | |

B is twice of C so C is half of B so you have to replace c = x/2 you will get answer. |

Ranadeep said: (Aug 31, 2013) | |

Let, Age of C is x years. Then age of B is 2x years. And age of A is 2x+2 years. 2x+2+2x+x = 27. 5x = 25. Therefore x = 5. Therefore the age of B is 2x = 2*5 = 10 years. |

Vinitha said: (Feb 17, 2014) | |

Do you know any other methods to solve the sum friends? |

Maddy said: (Feb 20, 2014) | |

Hi guys! can anyone tell me how to consider "x" in these questions and father son type ques? |

Priya said: (Mar 10, 2014) | |

How come the age of A is 2X+2 years? |

Karan Vekariya said: (Mar 25, 2014) | |

Here, b = 2c and a = (b-2) then, (b-2)+b+b/2 = 27. =>5b = 50. So, b = 10. |

Manoj said: (Jul 23, 2014) | |

Is there any shortcut method to solve question in examination hall? |

Puranjan Sahu said: (Jul 29, 2014) | |

Hi, You are telling A+B+C=27. And your answer of B's age is 10. Then how can you calculate the total age of all child as per your question suppose A=8, B=10 & C=12 then the total is 8+10+12=30. |

Thiru said: (Sep 22, 2014) | |

Hi, As per the question a+b+c=27, here a= b as of now reduced two years from b. So here b=a+2 years, c value is twice value of b, so which mean b*2. |

Anuj Rojlove said: (Mar 15, 2015) | |

Friends this question solve easy trick. Lets start assume. C = x. Then A = 2+B. But B = 2C {its twice of C}. So B = 2x {C = x (assume)}. Now question. A+B+C = 27. (2+2x)+2x+x = 27. = 2+5x = 27. = 5x = 27-2. = 5x = 25. x = 5. Then B = 2x (how old B). B = 2*5. B = 10 (answer). |

Al1Cee said: (Apr 16, 2015) | |

A+B+C = 27. Let A = B-2. B = It self. C = 2B (B is twice older than C). Substituting the givens A+B+C. B-2+B+2B = 27. 4B = 27+2. B = 29/4. B = 7. |

Gowthami said: (Jun 9, 2015) | |

Anyone answer me why we are not getting the answer if we substitute b=x? |

V!Cky said: (Sep 5, 2015) | |

A+B+C = 27. C is x. B is 2x. A is 2x + 2. 5x+2=27. 5x = 25. x = 5. |

Vinayak said: (Sep 24, 2015) | |

A = B+2. C = 2B. A+B+C = 27. B+2+B++2B = 27. 4B = 25. B = 6.25. I got this. :). |

Shrutika Gadhe said: (Nov 20, 2015) | |

Let the age of B be 2x. Ten the age of A will be 2x+2. And the age of C will be x. After that, x+2x+2+2x = 27. = 3x+2x+2 = 27. = 5x+2 = 27. = 5x = 27-2. = 5x = 25. x = 25/5. x = 5. Therefore the age of B 2x = 2*5 = 10. |

Hayat said: (Dec 5, 2015) | |

Let B=x. Then according to 1st condition. A=2+B (B=x). So A=2+x. 2nd condition B=2C so C=B/2 (B=x). C=x/2. Add A, B and C. A+B+C=27. (2+x) + (2 (x/2) ) + (x/2) =27. Simplify the equation. 5x+4=50. X=10 (option D ans). |

Xyz Abc said: (Mar 24, 2016) | |

B = x, A = x+2, C = 1/2x. Right? |

Suraj said: (May 5, 2016) | |

If b = x, then, a = 2 + x c = 2 + 2 + x = 4 + x. Then, a + b + c = 27. (2 + x) + x + (4 + x) = 27. 3x = 27 + 2 + 4. x = 33/3. x = 10. |

Shriram Nagorao Deshmukh said: (Jul 4, 2016) | |

A = 2 + B. B = 2C -> Eq 1. A + B + C = 27 -> Eq 2. Put value of A and B in 2, 2 + 2C + 2C + C = 27, 2C + 2C + C = 27 - 2, 2C + 2C + C= 25, 5C = 25, C = 5, Put C in eq 1, B = 2 * 5, B = 10. |

Sonam said: (Jul 31, 2016) | |

Solve this. The three sibling in a family is Anu, Rita, Bunu. Rita age is four years older than Anu and Bunu is Two years older than Rita. The sum of their ages is 40. Bunu age is? |

Saro said: (Aug 17, 2016) | |

A = 2 + B, B = 2C, A + B + C = 27. So, (2 + B) + B + B/2 = 27, 2B + B/2 = 25, 5B/2 = 25, B = 10. |

Dhinu said: (Sep 6, 2016) | |

Remember as "is" implies "=". |

Sagar said: (Dec 20, 2016) | |

According to me, the answer is 9. |

Sairam.B said: (Jan 20, 2017) | |

Thank you @Kalai. |

Shahid101 said: (Feb 1, 2017) | |

Lets. A=B+2. From this we have B=A-2. Then, B=2C. We have C=B/2. Add all these, A + B + C = 27. Put the values of A B and C. B + 2 + A-2 + B/2 =27. After solving, we will have. 3B + 2A = 54. We want B's age, so put that value of B which is in terms of A. 3B+2 (B+2) =54. Ultimately we have B=10. Correct me if I'm mistaken anywhere, please. |

Snehal said: (May 26, 2017) | |

Please, explain in detail how it comes 5x+2=27? |

Prashant Singh said: (Jun 2, 2017) | |

If, A is three times older than B, C is half the age of D, B is older than C. than what is the correct answer? (a) A is older than D (B) B is older than D Please tell me with the explanation. |

Pavani said: (Jul 16, 2017) | |

If we do option verification, option C(ans 9) is satisfying. i.e. 11+9+7=27. |

Sreeja said: (Jul 24, 2017) | |

If we take b as x then 9 is correct ans. 2+x+x+x-2 = 27, X = 9. |

Pranav said: (Dec 13, 2017) | |

The right answer is 7. |

Rebekah said: (Dec 17, 2017) | |

Can anyone explain 5x = 25? |

Sanjay said: (Jan 16, 2018) | |

Let, Age of C is x years. Then the age of B is 2x years. And the age of A is 2x+2 years. 2x+2+2x+x = 27. 5x = 25. Therefore x = 5. Therefore the age of B is 2x = 2*5 = 10 years. |

P.Gangadhar said: (Feb 8, 2018) | |

A is x. B is x-2. C is (x-2)/2. The sum of all ages is 27. x+ (x-2)+ (x-2)/2 = 27. (x-2+2x-4+2x) / 2 = 27. Then (x+2x-6+2x) = 54. (5x-6) =54. 5x =60. x= 12 then. (A is 12). B is (x- 2 = 12-2= 10). B age is 10. |

Sowji Budigi said: (Sep 1, 2018) | |

C is x. B is 2x,. A is 2x+2. 2x+2+2x+x=27. 5x+2=27. 5x=25. X=5. Then, B age is 2x so, 2*5=10. |

Zeeshan Ali said: (Jan 7, 2019) | |

Thanks all for explaining the answer clearly. |

Mahesh Bist said: (Apr 3, 2019) | |

Here, let B= x then A= 2+x then always c= x/2. According to question, A+B+C = 27, (2+x)+x+x/2 = 27, 5x+4 = 27*2, x = 50/5, x = 10. |

Sony said: (Apr 25, 2019) | |

Older means it should be age of A is x-2x, is it? |

Onkar said: (Jul 13, 2019) | |

A+B+C=27 --->(1) A-B=2. B=2C. A-2C=2 --> (2). SUBTRACT eqn 1 from 2 . B + 3C = 25. BUT B = 2C C = 5. B = 10 A = 12. |

#### Post your comments here:

Name *:

Email : (optional)

» Your comments will be displayed only after manual approval.